Pendidikan Kesehatan Mencuci Tangan 6 Langkah Terkait Kewaspadaan Penularan COVID-19 Aisyiyah Ranting Glundengan Cabang Wuluhan-Jember - Darotin, Rida; Fatarona, Anita (Journal of Health Innovation and Community Services, 2022)
Background: The first mysterious case of respiratory disorders came from Wuhan, Hubei Province. The media that became the source of transmission in this case is still not known for certain, this virus can be transmitted from human to human and has spread widely. People who are most at risk of contracting this disease are people who are in close contact with Covid-19 patients, including those who care for Covid-19 patients. Standard recommendations to prevent the spread of infection are through regular hand washing with soap and clean water, practicing cough and sneezing etiquette, avoiding direct contact with livestock and wild animals and social distancing with anyone showing symptoms of respiratory illness. Objective: increase the vigilance of the mosque congregation (women) regarding the transmission of covid-19 in the new normal era through health education, washing hands 6 steps during this pandemic is considered very necessary. Methods: Health education was carried out using lecture and discussion methods as well as monitoring success by observing mosque congregations (girls) in demonstrating 6 steps of hand washing. Results: The form of evaluation and achievement targets in this activity is to improve health status by increasing knowledge of Hand Washing 6 Steps to Increase Awareness related to Covid-19 Transmission in the New Normal Era. Conclusion: The indicator of success in the form of questions and answers at the end of the implementation session showed that most (85%) were able to answer questions smoothly and well.